Le teorie, le tecniche, i repertori figurativi nella prospettiva d'architettura tra il '400 e il '700 Dall'acquisizione alla lettura del dato - BARTOLI, MARIA TERESA; Lusoli, Monica (Studi e saggi, 2015)
The Modern Age perspective was born as a bridge between art and science. It made art necessary and science visible; its breeding ground was architecture, which has always involved the lovers of one and the other in synergy. The field of thought in which perspective was conceived focused on the highest topics: the universe and the earth. Starting from astronomers-geographers and topographers, perspective was built over time as a discipline and a scientific-artistic method, systematically deriving a theorem from another, in a crescendo of complexity, which has sometimes taken on acrobatic forms, not open to evidence. The perspective techniques developed over time have accompanied the figures of architecture and of the graphic arts in their changes. Nowadays, the current information technologies make it possible to study the models of this artistic field with the confidence of being able to bring to light a new story about it. This volume collects the essays of 44 researchers who, within an Italian National Project launched in 2011 and coordinated by Riccardo Migliari (from Rome), joined the call of the group in Florence, which Maria Teresa Bartoli directed, in order to illustrate their method of cultural and technical approach to the theme through a case study: be it represented by a painting or by the passages of a treatise.